First study to describe the prevalence and epidemiology of African swine fever, classical swine fever, porcine reproductive and respiratory syndrome and swine flu in Kazakhstan - Yuliya V. Perfilyeva; Elina R. Maltseva; Yekaterina O. Ostapchuk; Andrey V. Zhigailov; Anna S. Nizkorodova; Alena S. Cherusheva; Dinara A. Naizabayeva; Zhanna A. Berdygulova; Akerke O. Bissenbay; Tatyana V. Kuznetsova; Saltanat A. Kuatbekova; Gulnara A. Ismagulova; et al. (BMC Veterinary Research)
Abstract Background Kazakhstan, the ninth-largest country in the world, located in Central Asia and bordering China, Kyrgyzstan, Russia, Turkmenistan, and Uzbekistan, hosts a diverse population of domestic pigs across various environments, providing potential hosts for highly pathogenic viral diseases of swine. Here we monitored African Swine Fever Virus (ASFV), Classical Swine Fever Virus (CSFV), Porcine Reproductive and Respiratory Syndrome Virus (PRRSV), and Swine Influenza Virus (SIV). Results During the spring and fall of 2019, we sampled 1,459 domestic pigs in northern, central and eastern Kazakhstan. Samples were tested for antibodies by ELISA and for viral genomes by qPCR and RT-qPCR. No antibodies against ASFV or ASFV DNA were detected in sampled animals. Of the 84 farms sampled, 16.6% had at least one animal vaccinated against CSF. Seropositive pigs were found on a farm in Oskemen with no history of vaccination against CSFV. No CSFV RNA was detected in the blood of the sampled animals. Only 12.2% of the animals tested were vaccinated against PRRS with live-attenuated vaccines. The true animal-level seroprevalence of PRRS on unvaccinated farms was 16.6%. PRRSV RNA was detected in 17 unvaccinated animals in Pavlodar oblast on farms that were vaccinated against PRRS. The identified PRRSV-1 strains belonged to subtype 1 and clustered with the PRRS DV vaccine virus strain. A large proportion of the pigs had antibodies against SIV, with true animal-level seroprevalence of 35.9% and herd-level seroprevalence of 23.2%. Antibodies against the influenza A viruses of hemagglutinin subtypes H1 and H3 were found in the examined pigs. None of the animals were vaccinated against SIV. The variable 'commercial farming' showed an association with PRRSV and IAV seroprevalence. Of the unvaccinated farms, 9% were co-infected with PRRSV and SIV. Conclusions Results confirm the domestic pig population in Kazakhstan was not infected with ASFV but indicated exposure to PRRSV and SIV. This underscores the need for monitoring these infections in the region to manage their impact.